(untitled) (Південний архів (історичні науки), 2025)
Objective: The aim of this study is to explore the life and scientific career of the Ukrainian ornithologist and conservationist Oleksandr Oleksiiovych Shummer (1875–1938), to analyse his contribution to the development of national ornithology, wetland studies, and nature conservation, and to outline his place in the history of science within the context of the social and political challenges of the first third of the 20th century. Additionally, the study seeks to highlight the relevance of O.O. Shummer’s legacy for contemporary national historical memory. Methods: An interdisciplinary approach was employed, combining elements of the history of science, biography studies, social history, and memory studies. Methods used included biographical analysis, historical-documentary research, and content analysis of archival materials, particularly personal documents, investigation files, contemporaries’ memoirs, and O.O. Shummer’s scientific works. A comparative-historical method was also applied to analyse changes in the scholar’s scientific and public activities depending on the socio-political context. Research Results: The main stages of O.O. Shummer’s development as a scientist, conservationist, and public figure have been identified. His participation in scientific research, particularly the study of birds and wetland ecosystems of Southern Ukraine, has been highlighted. Special attention is given to his activities at the «Askania-Nova» Reserve, his efforts to popularize natural science knowledge among the public, and his practical initiatives for nature protection. The circumstances of his political persecution in the 1930s, which were part of broader repressive processes against the Ukrainian intelligentsia during the Stalinist regime, have been investigated.The study also addresses the silencing of Shummer’s name during the Soviet era and contemporary efforts to restore his place in historical memory. Conclusions. The research into Oleksandr Oleksiiovych Shummer’s biography confirms his significant role in the development of Ukrainian ornithology and nature conservation. Shummer successfully combined active scientific work with practical efforts in conservation and public education. His tragic fate reflects the dramatic processes of repression against the Ukrainian scholarly community. Recognizing his contribution is an important step toward restoring historical justice and strengthening national memory.